Student Academic Fraud and Implications in Guidance and Counseling Services - Maretta, Elsa Astya; Sukma, Dina (Current Issues in Counseling, 2023)
Academic honesty is important for students to have. However, in reality there are still many students who commit fraud. This study aims to describe the academic fraud of FIP UNP students based on the aspects of pressure, opportunity and justification. This research uses a quantitative approach with descriptive methods. Determination of the sample in this study using a purposive sampling technique and determined as many as 105 samples. The instrument used for data collection in this study was an academic cheating instrument with a Likert Scale model. Data is processed using interval and percentage formulas. Based on the results of this study, it was revealed that 1) Academic fraud as a whole was in the moderate category with a percentage of 71.43%. 2) Academic cheating is seen from the aspect of pressure with a percentage of 54.29%. 3) Academic cheating is seen from the aspect of opportunity with a percentage of 85.71%. 4) Academic cheating seen from the justification aspect is in the medium category with a percentage of 49.52%.